KELEMBAGAAN DAN KEWENANGAN PENGADILAN NIAGA TENTANG UPAYA HUKUM KEBERATAN TERHADAP PUTUSAN KOMISI PENGAWAS PERSAINGAN USAHA - Iriawan, Asep Iwan (Faculty of Law, Parahyangan Catholic University, 2024)
Article 24A (5) of the 1945 Constitution regulates the composition, position, membership, and procedural law of the Supreme Court and subordinate judicial bodies. Initially limited to bankruptcy, postponement of debt payment obligations (PKPU), and commercial matters by Law Number 37 of 2004, the jurisdiction of the Commercial Court has expanded through other laws. This expansion raises two key issues: (1) The need for legal remedies for objections to decisions of the Competition Supervisory Commission (KPPU), and (2) The competence of the Commercial Court to address these objections. This research uses a normative juridical method, suggesting that legal remedies for objections to KPPU decisions should be regulated in a separate law, addressing decisions from institutions beyond the judiciary’s jurisdiction. The procedural aspects for contesting KPPU decisions, outlined in Article 45 of the Omnibus Law Number 6 of 2023, should first be determined within the competence of the Commercial Court as regulated by law. The current institutional arrangements and authority of the Commercial Court, as outlined in the Bankruptcy and PKPU Laws and laws on Intellectual Property Rights, should be revised through a dedicated Law on Commercial Courts. This law should define the court's structure, powers, procedural rules, and set time limits and sanctions for case resolution at both the Commercial Court and the Supreme Court.